The explorations of the awareness, contemplation, self-Efficacy, and readiness of advance care planning, and its predictors in Taiwanese patients while receiving hemodialysis treatment - Li-Chen Chen; I-Te Tu; I-Chen Yu; Tao-Hsin Tung; Hsiang-Ping Huang; Yung-Chang Lin; Randal D. Beaton; Sui-Whi Jane (BMC Palliative Care, 2022)
Abstract Background End-stage renal disease (ESRD) is a major chronic illness worldwide, and Taiwan reports one of the highest incidence rates of ESRD with 529 cases per million population (pmp). A number of patients with ESRD patients might require lifelong hemodialysis (HD) or peritoneal dialyses (PD). Due to the progression of dialysis, patients are likely to experience other chronic comorbidities, anxiety and depression, frequent hospitalizations, and higher rates of mortality compared to patients with other types of chronic illnesses. As a result, dialysis patients are prone to experience advance care planning (ACP) needs, such as whether they withdraw from receiving dialysis while approaching their end-of-life (EOL). Yet, existing studies have shown that dialysis patients seldom receive timely consultation regarding ACP and there are limited studies examining ACP amongst Taiwan HD patients. Purpose The purpose of this study was to examine ACP awareness, contemplation, self-efficacy and readiness; and factors influencing ACP readiness. Design This cross-sectional descriptive study with convenience sampling was conducted in the out-patient HD unit at a regional teaching hospital in southern Taiwan. A total of 143 ESRD patients undergoing HD treatments were recruited. A 55-item ACP engagement survey containing the subscales of awareness, contemplation, self-efficacy, and readiness was employed. The data were analyzed with t-tests, one-way ANOVAs, Pearson’s correlations and multiple regressions. Results The results of our investigation revealed that approximately half of the participants (n = 67, 46.9%) were not informed of ACP. Although they reported considering their EOL, medical decisions and desired care, they demonstrated significantly low self-efficacy in discussing ACP (t= -5.272, p < 0.001). HD duration influenced all four ACP subscales; religious beliefs significantly influenced ACP-self-efficacy and readiness; and marital status, education, and primary decision-maker status significantly influenced ACP-readiness. The predictors of ACP-readiness were high self-efficacy and being the primary decision-maker (Adjusted R2 61%). Conclusion Most of the HD patients in this study had low ACP-awareness, contemplation, self-efficacy, and readiness, and most had not completed any ACP-related advance directives (AD). Healthcare professionals should proactively provide HD patients with ACP-related information and answer patients’ and medical decision-makers’ questions in a timely manner, thereby improving the quality of EOL care.